Impact of leadership styles and organisational citizenship behaviours on organisational green innovation performance: the moderating role of organisational legitimacy - Zhao, Shuliang; Renxi, Wu; Giglio, Carlo; Appolloni, Andrea (Wiley, 2025)
Firms' green innovation performance is influenced by several factors, including external legitimacy pressures and internal leader–member exchange relationships. Existing studies make little distinction between types of sustainable innovation and neglect leader, employee and organisational factors in the same strategic management framework. Based on institutional and social exchange theories, data from 537 Chinese enterprises are analysed through a hierarchical regression to explore how different leadership styles, organisational citizenship behaviours and legitimacy outside organisations affect green innovation performance. Research findings suggest that both transactional and transformational leadership contribute to organisational citizenship behaviours and green innovation performance. Organisational citizenship behaviours partially mediate between leadership styles and green innovation. Organisational legitimacy only positively moderates between leadership styles and organisational citizenship for green product innovation. This implies that organisations should pay attention to fostering high‐quality leader–member exchange relationships, formulating sustainable innovation management strategies and seeking a balance between obtaining organisational legitimacy and promoting organisational citizenship.
Keywords: green innovation performance; innovation management strategy; leadership styles; organisational citizenship behaviour; organisational legitimacy; sustainable innovation; 35 Commerce, Management, Tourism and Services; Business & Management; 3501 Accounting, auditing and accountability; 3502 Banking, finance and investment; 3507 Strategy, management and organisational behaviour